2019
DOI: 10.1111/imm.13139
|View full text |Cite
|
Sign up to set email alerts
|

The impact of lung microbiota dysbiosis on inflammation

Abstract: SummaryHost−microbiota interaction plays fundamental roles in the homeostasis of mucosal immunity. Dysbiosis of intestinal microbiota has been demonstrated to participate in various immune responses and many multifactorial diseases. Study of intestinal microbiota has moved beyond the consequences of dysbiosis to the causal microbiota associated with diseases. However, studies of pulmonary microbiota and its dysbiosis are still in their infancy. Improvement of culture‐dependent and ‐independent techniques has f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 105 publications
1
41
0
2
Order By: Relevance
“…Although the causal link between lung microbiota and BPD has not been fully demonstrated, it can be assumed that the lung maladaptive microbiome is an effective driver for other potentially harmful factors in this illness (24). Dysregulation of the lung microbiota elicits local or systemic infection/inflammation, activates the immune response (25)(26)(27), and is related to oxidative stress and metabolic disorders in the host (24), which impairs dysbiosis, thus creating a vicious circle involved in the disease onset and exacerbation.…”
Section: Bpd and Lung Microbiota Dysbiosis Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the causal link between lung microbiota and BPD has not been fully demonstrated, it can be assumed that the lung maladaptive microbiome is an effective driver for other potentially harmful factors in this illness (24). Dysregulation of the lung microbiota elicits local or systemic infection/inflammation, activates the immune response (25)(26)(27), and is related to oxidative stress and metabolic disorders in the host (24), which impairs dysbiosis, thus creating a vicious circle involved in the disease onset and exacerbation.…”
Section: Bpd and Lung Microbiota Dysbiosis Associationmentioning
confidence: 99%
“…The inflammatory reaction attributable to the lung maladaptive microbiota may also be closely related to Th17 activation (27). In this regard, the lung microbiota has been shown to modulate local mucosal barrier function by enhancing or reducing the release of IL-17 family cytokines, which are mainly secreted by Th17 cells (26). However, microbiota dysbiosis may activate pulmonary fibrosis by stimulating IL-17B production, which in turn acts on Th17 and neutrophil recruitment genes under TNF-α coordination in a feedback event (53).…”
Section: Infection/inflammationmentioning
confidence: 99%
“…Regarding the homeostatic situation, research in recent years has revealed that in contrast to the older view of the lungs as sterile organs, a lung microbiota is present in the lower airways which exerts significant effects in health and disease, although it is not as abundant as in the gut (29)(30)(31)(32). The term "microbiota" refers to all the microorganisms present, namely bacteria, fungi, protozoans, and viruses (29), but here we will only consider the role of bacteria.…”
Section: Nk Cells In the Lungsmentioning
confidence: 99%
“…Everything that disturbs this balance, such as some medications and particularly antibiotics, increases in nutrients (high fat diet, low fiber diet), cigarette smoke, infectious agents, chronic inflammation, can disturb the gut as well as the lung microbiota and lead to a state of dysbiosis, characterized by an increased number of airway bacteria and a change in its composition. The dysbiosis is profoundly linked to several severe lung diseases [asthma, chronic obstructive pulmonary disease (COPD), infections, cancer] (29)(30)(31)(32)(33)(34)(35).…”
Section: Nk Cells In the Lungsmentioning
confidence: 99%
“…When functional or compositional modi cations (i.e. dysbiosis) occur, the protecting role of the microbiota in maintaining a stable and suitable environment may be altered, in uencing the immune system activity, thus favoring the expansion of pathobionts [18][19][20]. Dysbiosis has been detected in the inferior turbinate mucosa of AR patients, showing a decreased microbiome diversity and an anaerobic taxa enrichment [21].…”
Section: Introductionmentioning
confidence: 99%